Efectos fisicoquímicos y sensoriales de relaciones lactosuero - leche y porcentajes de pulpa de pitahaya en una bebida láctea - Bravo González, Jenniffer Joana (2025)
The purpose of this research was to determine the physicochemical and sensory effects induced by the factors under study. A two-factor design in a Completely Randomized Design (CRD) was used, with Factor A being the whey-lactose-free milk mixture (40-60, 50-50, and 60-40 ratios) and Factor B being pitahaya pulp (10%, 15%), with three repetitions, resulting in 18 experimental units of 350 mL each. The physicochemical variables measured included fat, lactose, and protein, while the sensory analysis was performed using a preference ranking test. The results from the physicochemical analyses showed that lactose and fat variables had higher averages in Treatment 1 (40% whey and 60% lactose-free milk) with values of 4.54% and 1.96%, respectively. Protein, not meeting the assumption of normality, was evaluated with non-parametric tests such as Kruskal-Wallis and Mann-Whitney U tests, with Treatment 1 showing the highest mean (2.73%). Similarly, the sensory analysis determined that Treatment 1 received the highest acceptability from untrained tasters. These analyses suggest that the beverage composition, particularly the milk proportion, significantly influences both its physicochemical properties and its sensory perception.